Pedagogical Pragmatism of Islamic Education Teachers in Implementing Holistic Assessment in Senior High School - Anisa Nur Sajidah; Saepul Anwar; Usup Romli (Nuris Journal of Education and Islamic Studies, 2026)
This article examines the adaptive strategies of Islamic Religious Education (hereafter IRE) teachers in implementing holistic assessment, which frequently encounters logistical constraints in schools. Unlike previous studies that focus on administrative compliance, this research highlights the professional agency of educators to fill a phenomenological gap. Employing a qualitative case study on three IRE teachers in secondary education, data were collected through in-depth interviews, observations, and document analysis. The findings indicate that teachers respond to systemic pressures through pedagogical pragmatism. These strategies encompass the simplification of cognitive instruments into Lower Order Thinking Skills (LOTS), the modification of psychomotor practices, and a transition toward intuitive observation in the affective domain. In conclusion, such compromises are not indicative of incompetence, but rather a manifestation of adaptive intelligence to safeguard the essence of ta'dib amidst rigid curriculum standardization.